Denmark : Financial Sector Assessment Program-Technical Note-Review of Danish Capital Market. (IMF Staff Country Reports; Country Report, 2007)
This technical note discusses the structure of the Danish capital market and related issues. The focus is on the organization and functioning of domestic securities markets. The note provides a regional perspective on these markets. It reviews the prudential framework for capital markets, and analyzes the progressive integration and collaboration among the Scandinavian stock exchanges. The note also discusses liquidity in Danish capital markets, as well as analyzes the rapid growth of Danish investment funds.